2021
DOI: 10.4081/monaldi.2021.1649
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rate and time to serious adverse events among rifampicin resistant tuberculosis patients in Georgia treated with new and repurposed anti-tuberculosis drugs, 2016-2018

Abstract: Considering the complexity of second-line anti-tuberculosis (TB) treatment regimens, the management of drug-resistant TB (DR-TB) in Georgia remains a major challenge. Since the introduction of new and repurposed anti-TB medications, the implementation of active TB Drug Safety Monitoring (aDSM) was a critical program component to help establish safety and manage all treatment related Serious Adverse Events (SAEs). In our study, we aimed to describe the occurrence, characteristics and timing of SAE among patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The reason for this difference is because our population had more people with ADE risk factors, such as HIV, aminoglycosides-based regimen and longer treatment durations, while the other study focused on newer shorter treatment regimens in predominantly HIV negative population. 20 The findings from our study could be an underestimate of the true From our study, a drug regimen containing an aminoglycoside (Am, Km, Cm) or linezolid or pyrazinamide were associated with the occurrence of an ADEs. This is consistent with findings from a systematic review that reported that ADEs leading to permanent discontinuation were associated with aminoglycosides and Lzd.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The reason for this difference is because our population had more people with ADE risk factors, such as HIV, aminoglycosides-based regimen and longer treatment durations, while the other study focused on newer shorter treatment regimens in predominantly HIV negative population. 20 The findings from our study could be an underestimate of the true From our study, a drug regimen containing an aminoglycoside (Am, Km, Cm) or linezolid or pyrazinamide were associated with the occurrence of an ADEs. This is consistent with findings from a systematic review that reported that ADEs leading to permanent discontinuation were associated with aminoglycosides and Lzd.…”
Section: Discussionmentioning
confidence: 54%
“…The reason for this difference is because our population had more people with ADE risk factors, such as HIV, aminoglycosides-based regimen and longer treatment durations, while the other study focused on newer shorter treatment regimens in predominantly HIV negative population. 20 The findings from our study could be an underestimate of the true value because the clinicians and patients could have under reported the ADEs during the review visits, particularly those that were mild or moderate.…”
Section: Discussionmentioning
confidence: 72%